Distinct overlapping functions for Prickle1 and Prickle2 in the polarization of the airway epithelium - Kunimoto, Koshi; Weiner, Alexis T.; Axelrod, Jeffrey D.; Vladar, Eszter K. (Frontiers in Cell and Developmental Biology, 2022)
Planar cell polarity (PCP) signaling polarizes cells within the plane of an epithelium. In the airways, PCP signaling orients the directional beating of motile cilia required for effective mucociliary clearance. The PCP signaling mechanism is best understood from work in Drosophila, where it has been shown to both coordinate the axis of polarity between cells and to direct the morphological manifestations of polarization within cells. The ‘core’ PCP signaling mechanism comprises two protein complexes that segregate to opposite sides of each cell and interact with the opposite complex in neighboring cells. Proper subcellular localization of core PCP proteins correlates with, and is almost certainly responsible for, their ability to direct polarization. This mechanism is highly conserved from Drosophila to vertebrates, though for most of the core genes, mammals have multiple paralogs whereas Drosophila has only one. In the mouse airway epithelium, the core protein Prickle2 segregates asymmetrically, as is characteristic for core proteins, but is only present in multiciliated cells and is absent from other cell types. Furthermore, Prickle2 mutant mice show only subtle ciliary polarity defects. These observations suggest that other Prickle paralogs might contribute to polarization. Here, we show that Prickle1 segregates asymmetrically in multiciliated and nonciliated airway epithelial cell types, that compared to Prickle 2, Prickle 1 has different spatial and temporal expression dynamics and a stronger ciliary polarity phenotype, and that Prickle1 and Prickle2 mutants genetically interact. We propose distinct and partially overlapping functions for the Prickle paralogs in polarization of the airway epithelium.